Preventing Repeat Incidents of Family Violence: A Reanalysis of Data From Three Field Tests in Manhattan (New York City), New York, 1987, 1995-1997 - Davis, Robert C. ([Verlag nicht ermittelbar], 2011)
In the mid-1980s New York City officials developed an intervention program, the Domestic Violence Intervention Education Project (DVIEP), to reduce repeat incidents of family abuse. The program posited that repeat victimization would decline as victims extracted themselves from self-defeating relationships or by working with social services and criminal justice staff to develop strategies to end the abuse while staying in the relationship. The purpose of this study was to evaluate the effectiveness of the DVIEP model in reducing repeat instances of family violence. Between 1987 and 1997, three separate, randomized field experiments in New York City's public housing projects evaluated whether or not the DVIEP program reduced the rate of subsequent victimization. All three studies tested the same intervention model: persons who reported family violence to the police were randomly assigned to receive or not to receive a follow-up visit from a domestic violence prevention police officer and a social worker. For this study, researchers concatenated the micro data from the 3 experiments into a single, 1,037 case dataset that contains identical treatment and control measures, and nearly identical outcome measures. Of the 1,037 total cases in the study, 434 are from the 1987 Domestic Violence Study, 406 are from the Elder Abuse study, EFFECTIVENESS OF A JOINT POLICE AND SOCIAL SERVICES RESPONSE TO ELDER ABUSE IN MANHATTAN [NEW YORK CITY], NEW YORK, 1996-1997 (ICPSR 3130), and 197 are from the Domestic Violence Arrestee Study in Manhattan's Police Services Area 2 (PSA2). The resulting data collection contains a total of 31 variables including which study (1987 Domestic Violence Study, Elder Abuse Study, or Domestic Violence Arrestee Study) the respondent participated in, whether the respondent was part of the experimental group or the control group, whether the respondent received public education or a home visit by a DVIEP team, the number of DVIEP services the respondent used, and whether the respondent completed a final interview with a DVIEP team after six months of tracking. Additionally, variables include the victim's age, whether the perpetrator of domestic abuse was a romantic partner of the victim, the number of incidents reported to the police, the Conflict Tactics Scale (CTS) violence score, and the number of days until the first new incident of domestic abuse.